Improving Performance, Value, and Quality of Environmental and Improvement Aspects by 10% through the Gemilang Program - Aifah Aifah; Reggina Shafira Luthi; Trio Aris C; Wahyu Saputra; M. Osaegi A (Journal of Social Research, 2025)
The mining industry globally faces increasing pressure to enhance environmental performance and foster continuous improvement. According to the World Bank (2023), sustainable mining practices are critical for long-term operational viability, while McKinsey (2023) reports highlight that companies with robust environmental management systems achieve 15–20% better stakeholder confidence and regulatory compliance. The Gemilang Program is a continuous improvement initiative implemented at PT Putra Perkasa Abadi (PPA) Site BIB, aimed at enhancing the performance, value, and quality of the Environmental (LH) and Improvement aspects in the evaluation of Subcontractor Operational Responsible Persons (PJO). Based on the evaluation results of the second semester of 2024, the Environmental and Improvement aspect scores were 62.3 and 43.43, respectively (categorized as red–blue). These low scores pose significant implications for the sustainability rating and environmental reputation of national mining companies operating under stringent regulatory frameworks. Through the implementation of the Gemilang Program, various measures such as intensive mentoring, training, provision of standardized evaluation formats, and a reward-and-punishment system successfully improved the scores in the first semester of 2025 to 69.38 for the Environmental aspect and 61.09 for the Improvement aspect. These results represent significant increases of 11.36% and 40.66%, demonstrating the program’s effectiveness in fostering a work culture focused on continuous improvement.